Proceedings - Smith, George Leonard, 1935-, editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1979)
Workshop in Instream Flow Habitat Criteria and Modeling (1978: Colorado State University).
Keywords: Stream measurements -- Data processing -- Congresses; Stream measurements -- Mathematical models -- Congresses; Fisheries -- Hydrologic factors -- Data processing -- Congresses; Fisheries -- Hydrologic factors -- Mathematical models -- Congresses